PENGARUH BEBAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING STUDI KASUS PADA PT SINAR SOSRO KPB MOJOKERTO - SISKA JUNIATI, FIFIANA (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this study is to examine and analyze the effect of workload on employee performance through organizational commitment as intervening variable. This research is a causality research with quantitative approach. Technique of sampling using random sampling technique with amount 96 respondents at employees of PT Sinar Sosro KPB Mojokerto. Statistical analysis in this study is Partial Least Square (PLS) with the help of smartPLS 3.0 software. The results of this study explain that the workload has no effect on employee performance, workload has a positive and significant impact on organizational commitment,organizational commitment has a positive and significant impact on employee performance, and organizational commitment interferes with the effect of workload on employee performance.